2001
DOI: 10.1046/j.1523-1755.2001.0590051762.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 and osteopontin differentially regulate monocytes recruitment in experimental glomerulonephritis

Abstract: These studies show that chemokines and osteopontin are differentially expressed in glomeruli and tubules in this model of GN. Chemokines play a primary role in the glomeruli, whereas osteopontin has a predominant role in tubulointerstitial M/M recruitment. The roles of chemokines and osteopontin may thus be dependent on the renal compartment and on the disease model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 28 publications
1
80
1
Order By: Relevance
“…Earlier studies demonstrated that the expression of OPN correlates well with macrophage infiltration in various experimental models of renal injury. 42, 43 Persy et al 44 showed that the loss of OPN expression in OPN-deficient mice resulted in a significant reduction in macrophage infiltration and renal fibrosis in a murine model of ischemia reperfusion injury. In our current study, reduction of macrophage infiltration in UUO following MMP-9 inhibition was associated with a reduction in expression of MMP-cleaved OPN corresponding to the protein size of 32 kDa and not the expression of chemokine CCL-2, which was previously found to be a key macrophage chemoattractant in UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that the expression of OPN correlates well with macrophage infiltration in various experimental models of renal injury. 42, 43 Persy et al 44 showed that the loss of OPN expression in OPN-deficient mice resulted in a significant reduction in macrophage infiltration and renal fibrosis in a murine model of ischemia reperfusion injury. In our current study, reduction of macrophage infiltration in UUO following MMP-9 inhibition was associated with a reduction in expression of MMP-cleaved OPN corresponding to the protein size of 32 kDa and not the expression of chemokine CCL-2, which was previously found to be a key macrophage chemoattractant in UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…118,119 In addition, through thrombospondin 1, Ang II activates the release of active TGF␤ from the latent complex. 118,119 Finally, Ang II directly upregulates type 2 TGF␤ receptors by mediating transcriptional activity of the receptor gene. 36 tiation from tubular cells to macula densa cells can be controlled by angiotensin type 2 receptors (AT2Rs).…”
Section: Ang II and Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…118,119 In several models of kidney fibrosis with increases in local Ang II, endothelin simultaneously increases endothelin-1 (ET-1). 85,89 In a model of severe Ang II-dependent hypertension in Ren-2 transgenic rats, the role of Ang II, ET-1, and L-type calcium channels in the development of glomerular, vascular, and tubulointerstitial fibrosis is observed after treatment with irbesartan, bosentan, and a selective endothelin receptor antagonist.…”
Section: Ang II and Other Profibrotic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we propose that GM-CSF released by renal parenchymal cells increases the numbers of activated macrophages that are capable of releasing further inflammatory mediators (e.g., IL-1␤), previously demonstrated to be critical in the progression of GN (29). Mesangial cells produce MCP-1 in response to IL-1␤ (53); furthermore, blocking MCP-1 via Ab reduces glomerular injury and proteinuria (54,55). Hence, renal GM-CSF may regulate glomerular and tubular injury through MCP-1 by influencing IL-1␤ or in an autocrine feedback loop as renal cells have been demonstrated to be the principal producers of MCP-1 (56).…”
Section: Discussionmentioning
confidence: 91%